Perceptions of quality of care in Midwife-led Birth Centres (MLBCs) in Uganda: Why do women choose MLBCs over other options? - Nabirye, Rose Chalo; Mbalinda, Scovia Nalugo; Nawagi , Faith; Bazirete, Oliva; Homer, Caroline S.E. (Women and Birth, 2024)
Midwife-led birth centres (MLBCs) are associated with reduced childbirth interventions, higher satisfaction rates, and improved birth outcomes. The evidence on quality of care in MLBCs from low and middle-income countries (LMIC) is limited.